2022
DOI: 10.1371/journal.pone.0261332
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of common infectious diseases in Japan during the COVID-19 pandemic

Abstract: Recent reports indicate that respiratory infectious diseases were suppressed during the novel coronavirus disease-2019 (COVID-19) pandemic. COVID-19 led to behavioral changes aimed to control droplet transmission or contact transmission. In this study, we examined the incidence of common infectious diseases in Japan during the COVID-19 pandemic. COVID-19 data were extracted from the national data based on the National Epidemiological Surveillance of Infectious Diseases (NESID). Common infectious diseases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
(42 reference statements)
4
19
1
Order By: Relevance
“…The decreasing fecal-oral-, vector-borne, and direct-contact transmitted NIDs during pandemic were consistent with previous studies in other countries [12] , [18] , [19] , [20] . In Netherland, gastrointestinal-related NIDs, such as norovirus disease, hepatitis A and shigellosis and travel-related NIDs, such as malaria, Zika, typhoid fever, cholera, yellow fever and paratyphus were reported 50% less often during the first wave of the COVID-19 epidemic than in the corresponding period in 2017–2019 [18] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The decreasing fecal-oral-, vector-borne, and direct-contact transmitted NIDs during pandemic were consistent with previous studies in other countries [12] , [18] , [19] , [20] . In Netherland, gastrointestinal-related NIDs, such as norovirus disease, hepatitis A and shigellosis and travel-related NIDs, such as malaria, Zika, typhoid fever, cholera, yellow fever and paratyphus were reported 50% less often during the first wave of the COVID-19 epidemic than in the corresponding period in 2017–2019 [18] .…”
Section: Discussionsupporting
confidence: 92%
“…Although the implementation of these NPIs was developed to contain COVID-19, many studies had showed it also help decrease the activity of other airborne/droplet-transmitted infectious diseases, such as influenza, invasive pneumococcal diseases (IPD), and measles [6] , [7] , [8] , [9] , [10] , [11] . In contrast, the effect of NPIs on the epidemiology of non-airborne/droplet-transmitted infectious diseases was rarely reported and most of them were conducted during the first wave of COVID-19 [12] , [13] , [14] , [15] , [16] , [17] . To better understand the long-term effect of COVID-19 on the activity of non-airborne/droplet-transmitted infectious diseases, this study was conducted to compare the case number of non-airborne/droplet-transmitted notifiable infectious disease (NID) between pandemic period and the pre-pandemic period.…”
Section: Introductionmentioning
confidence: 99%
“…It may seem surprising at first sight that during the partial lockdown period, on average, the general health of both adolescents and parents included in this research improved. However, this confirms some known data, namely that during this period, various infectious diseases such as tuberculosis and legionellosis declined, due to the limitation of interpersonal contacts and therefore, the risks of contamination ( (accessed on 12 March 2022)) [ 31 , 32 ]. In addition, the widespread use of masks, hydro-alcoholic gels, and social distancing certainly also had an impact beyond the prevention of COVID-19 alone.…”
Section: Discussionsupporting
confidence: 86%
“…Tuberculosis beds were a notable exception, however, with decreased numbers of inpatients but increased numbers of new hospitalizations. The decreased number of inpatients in likely attributable to the fact that rates of tuberculosis decreased in Japan during the pandemic [ 35 ]. Increased social distancing and masking decreased the aerosol transmission of tuberculosis, and decreased travel because of tight border restrictions essentially eliminated imported cases of tuberculosis.…”
Section: Discussionmentioning
confidence: 99%